1989
DOI: 10.1029/jb094ib11p15555
|View full text |Cite
|
Sign up to set email alerts
|

Wide‐angle triangulation array study of simultaneous primary microseism sources

Abstract: Persistent low frequency noise between 10 and 200 mHz due to storm systems is commonly observed as microseisms on seismic records from land and ocean bottom detectors. We report on an analysis of 20‐second microseisms recorded simultaneously on two land‐based long‐period arrays (the Alaskan Long Period Array and the Large Aperture Seismic Array) during November 1973. Azimuths of approach are determined by applying frequency wave‐number analysis and beam‐forming techniques to coherent bandpass‐filtered samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Wave-number spectra generated from data from several large continental seismic arrays suggest microsei sm energy is primarily associated with surface wave modes (Cessaro and Chen, 1989). These studies also identified the Gulf of Alaska as a common source for microseisms.…”
Section: Interelement Microseismic Coherencementioning
confidence: 65%
“…Wave-number spectra generated from data from several large continental seismic arrays suggest microsei sm energy is primarily associated with surface wave modes (Cessaro and Chen, 1989). These studies also identified the Gulf of Alaska as a common source for microseisms.…”
Section: Interelement Microseismic Coherencementioning
confidence: 65%
“…However, seismic arrays have been used extensively to determine the direction of approach of microseismic energy (Lacoss et al, 1969;Bungum et al, 1971;Capon, 1972;Cessaro and Chan, 1989;Cessaro, 1994;Friedrich, 1996;Friedrich et al, 1998;Essen et al, 2001). Microseisms observed in Central Europe, especially secondary microseisms, are generated most frequently near the (northern) Norwegian coast, the continental shelf off the British Isles, and the Atlantic coast of southern France and the Iberian Peninsula (Friedrich, 1996;Friedrich et al, 1998;Essen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Triangulation using the time delays of arrival of Z component seismograms between station pairs has been used to locate microseism sources [Cessaro, 1994]. f-k analysis has been used with Z components recorded at arrays of stations to determine the slowness and back azimuth [Cessaro, 1994;Cessaro and Chan, 1989;Friedrich et al, 1998;Schulte-Pelkum et al, 2004;Chevrot et al, 2007]. A polarization method, assuming Rayleigh-wave propagation, to calculate the back azimuth by measuring phase differences between horizontal and vertical components has also been used [Schulte-Pelkum et al, 2004;Chevrot et al, 2007;Stutzmann et al, 2009].…”
Section: Introductionmentioning
confidence: 99%